Contribution to cytotaxonomy of Silene: chromosome pairing and unreduced pollen grain formation in sec. Sclerocalycinae - Sheidai, Masoud (Acta Biologica Szegediensis, 2009)
Meiotic studies of ploidy level, chromosome paring and chiasma frequency were performed on 24 populations of nine Silene species belonging to the section Sclerocalycinae growing in Iran. The species studied are: 1- Silene bupleuroides L., 2- S. eremitica Boiss., 3- S. stapfii Melzh., 4- S. shahrudensis Rech. (two populations), 5- S. peduncularis Boiss. (two populations), 6- S. avromana Boiss. (three populations), 7- S. caesarea Boiss. (seven populations), 8- S. chlorifolia SM. , 9- S. swertiifolia Boiss. (six populations). The species studied showed 2n = 2x = 24. The chromosome numbers of all species are reported here for the first time. The species and populations studied differed significantly in chiasma frequency and chromosomes pairing indicating partly their genetic differences. When the species were subjected to cluster analysis based on meiotic characters almost the populations of each species were grouped together indicating their distinctness. Meiotic abnormalities including multipolar cell formation formed unreduced pollen grains in some of the species while B-chromosomes occurred in some others.